Environmental costs in Pinus radiata D. Don. forest plantations - Gayoso, Jorge (Bosque (Valdivia), 1996)
This study proposes a quantitative environmental assessment method. Economic consequences related to forest operations in Pinus radiata D. Don forests, under the concept of soil and water sustainable natural capital were modeled. Environmental costs consider the costs of mitigation actions required to reduce impact levels up to the impacts caused by the use of the best available technology. The model applies a standard costs matrix to an impact coefficient matrix according to the level of sensitivity of the soil. The result is valuation of environmental costs in monetary units per hectare. The model allows impartial assessment at company, regional and national levels. Three scenarios and technologic appropriateness levels were simulated. Environmental costs range from 2246 US$/ ha (5.61 US$/m3 ) to 1019 US$/ha (2.55 US$/m3 ) for both the use of inappropriate technology in traditional harvesting and the use of the best techniques in mechanized harvesting, respectively. Relating environmental costs with the annual harvesting rate of Pinus radiata D. Don forests in Chile - at high and moderate appropriateness levels, figures of 30 to 50 million US dollars per year were obtained. Main impacts are related to road construction, the use of prescribed fire for soil preparation practices and groundbased logging on wet soil conditions.